Asuhan Keperawatan Pada Ny.J Suspeks Kanker Serviks di RSUD Bekasi - Novi Triana; Merida Simanjuntak (AKPER Pasar Rebo, 2018)
One of the highest reproductive health problems at present is cervical cancer. Cervical cancer occurs characterized by the growth of cells in the cervix that are not unusual (abnormal) usually attack women aged 35-55 years. According to the 2015 International Agency For Research On Cancer (IARC), 85% of cancer cases in the world with a total of around 493,000 with a total of 273,000 deaths occur in developing countries like Indonesia. The role of nurses regarding cervical cancer problems can be prevented by promotive, preventive, curative and rehabilitative efforts. How is the description of the provision of nursing care in patients with cervical cancer in patients Mrs. J with suspected cervical cancer in Dr. Chasbullah Abdulmajid Hospital at Bekasi City. Aims to gain real experience in providing nursing care for patients suspected of cervical cancer. Implemented with a descriptive narrative method. There are 5 (five) diagnoses of pain associated with physical agents (surgical procedures), the risk of bleeding is evidenced by risk factors: lack of exposure to information about prevention of bleeding, malignancy process; Nutritional deficits are associated with the inability to digest food, anorexia; Knowledge deficits are associated with a lack of exposure to information, the risk of infection is evidenced by risk factors: invasive procedures. After two days of implementation, it was found that two problems were resolved and three that had not been resolved were pain, risk of bleeding and nutritional deficit.